Static Voltage Stability Evaluation and Correction Strategy Based on Stage Solving Strategy and SIFT - Yan Wen; Xiaoming Liu; Yongzhi Zhou; Huiwen Zhang; Donglei Sun (IEEE Access)
Aiming at the static voltage instability problem of the power grid caused by large-scale access of renewable energy sources, the study adopts the scale invariant feature transform algorithm for boundary feature extraction, while optimizing the traditional generalized resilience index of the power grid. An improved static voltage stability elasticity index is proposed for fast static voltage stability assessment. In addition, a time-domain rolling phase solution strategy is introduced to correct the static voltage stability. The results indicated that the boundary feature extraction method based on SIFT could effectively realize the extraction of boundary features and reflect the correlation between the network and the load. In the single-load and full-load growth scenarios, the improved elasticity metrics proposed by the study were consistent with the change trend of the traditional method and had higher sensitivity. In addition, in time phase 1 of the IEEE30 node system, the average value of load margin for each scenario in the first phase was 18.62 MW, which was below the load margin threshold. The power generation cost was only 577.1 yuan. In phase 3, the average load margin for each scenario increased to 19.71 MW, which was significantly higher than the load margin threshold, and the power generation costs were only 573.0 yuan. In time stages 2 and 3, the load margin of each scenario in the stage 1 was higher than the load margin threshold. In addition, the solution time of the time-domain rolling-based stage solving strategy was only 36.9s, which decreased by 10.9s compared to the interior point method. The study demonstrated that the proposed static voltage stability assessment and correction strategy enhances the accuracy and responsiveness of the power grid assessment. Concurrently, it ensures grid stability while preserving economic efficiency. This strategy is of considerable importance for facilitating the sustainable integration of large-scale renewable energy sources into the power grid.